Optimizing the Marketing Potential of BSF Maggot as a Decomposer of Organic Waste to Overcome Social Problems in Murtigading Village, Bantul, D.I. Yogyakarta - Hasanudin, Iman; Budianto, Yohan; Fauzi, Zuhud Ahnaf (Jurnal Indonesia Sosial Sains, 2024)
The improper management of organic waste has become a serious issue in Murtigading Village, Bantul, Yogyakarta. Black soldier fly (BSF) maggot cultivation offers an efficient solution for decomposing organic waste. However, the marketing of BSF maggots remains a challenge due to a lack of community knowledge and business strategies. This research aims to optimize the marketing potential of BSF maggots to address both waste management and social problems in the village. A descriptive qualitative method was employed, involving interviews, field surveys, and literature reviews. The study analyzed the strengths, weaknesses, opportunities, and threats (SWOT) of BSF maggot marketing, supported by a Pentahelix model that involves collaboration between the community, government, private sector, media, and academics. The results show that there is significant market potential for BSF maggots, with demand from industries in Surabaya requiring up to 5 tons of maggots per shipment. Furthermore, marketing through digital platforms like online shops offers a cost-effective solution for increasing sales, reducing the reliance on traditional methods. This research concludes that with improved marketing strategies and support from key stakeholders, BSF maggot cultivation could become a profitable industry while solving the village's waste problem.